Problems in establishment of clinical diagnosis and conducting the medical reporting on ICD-10 at gastroduodenal ulcers and NSAID-related gastropathies - I. A. Argunova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To draw attention to problems of the style of clinical diagnosis and its encoding at gastroduodenal ulcers and NSAIDs-related gastropathies according to ICD-10.Original positions. Multiplicity of causes of stomach and duodenum ulcers requires assessment of nosological belonging of gastroduodenal ulcers and changes of system of their registration in medical statistics. ICD-10 does not meet modern demands of differentiation of erosive and ulcerative lesions of the stomach and duodenum, combining them in a joint heading of «ulcer» equating thereby to peptic ulcer. Variants of improvement of their encryption in frameworks of ICD are presented.Conclusion. Change of erosive and ulcerative lesions encoding within ICD system results in specification of diagnosis at symptomatic gastroduodenal ulcers and NSAIDs-related gastropathies, development of differentiated approaches to their treatment and prophylaxis, improvement of statistical reporting.